PARAMETER POPULASI DAN POLA MUSIM PENANGKAPAN IKAN LAYANG (Decapterus spp) DI PERAIRAN MALUKU UTARA - Irham Irham; Sugeng H. Wisudo; John Haluan; Budy Wiryawan (Buletin PSP, 2008)
The scads (Decapterus spp) in North Maluku waters is highly potential and the utilization in developing phase. However, there is an indication of overexploited found in the coastal waters. The aims of this research are: (1) to determine population parameters of Decapterus macarellus based on the biological approach; and (2) to find out fishing season of the scads. The research was conducted from January to December 2008, in the North Maluku waters. Data for the research consisted of primary and secondary data. The data were analyzed using methods of the growth coefficient and the length infinity, the length-weight relationship, maturity level in fishes, estimating the size at first maturity in fishes, fecundity and moving average analyses. The results show that growth of female D. macarellus was quicker than masculine, and both had a maximum length-growth at the age of 4 year. Growth pattern of D. macarellus had a specific characteristic, called "minor alometrik", meaning that length-growth was quicker than weight-growth of the body. The catch of D. macarellus was dominated by inmature species. The most maturity of the D. macarellus was found in March. The size at first maturity was reached at a length of 25,8 cm. Spawning took place in April or May. Fecundity ranged from 28875 to 84000 eggs with a total length of 268 to 310 mm. Fishing season of scads occurred from March to October with the peak season in August.